True ileal phosphorus digestibility of soybean meal for male and female broiler chickens - Mirabile, Catharina Giovana (2021)
To determine the true ileal P digestibility coefficient of soybean meal (SBM), a total of 384 broilers (Cobb 500) at 21 days old, 192 males and 192 females, were arranged in a 3 х 2 (three total P levels x sex) factorial assay in a completely randomized design, with eight replicates and eight birds per experimental unit. The levels of total P in the experimental diets were 2.8, 3.5 and 4.2 g/kg. Increases in total P levels were achieved with the exclusive inclusion of SBM. Diets were provided from 21 until 26 days old, when the ileal digesta of the birds were collected. After chemical analyses, the ileal digestible P content of the diets was plotted against total P concentration in a linear regression analysis. The slope of the regression line gives the true ileal P digestibility coefficient of SBM. There was no interaction between sex and total P of diets (P > 0.05). There was linear increase in ileal P digestible content (P < 0.001) with increasing levels of total P in the diets, according to the equation Y = 0.419X+2.350. In conclusion, the true ileal P digestibility coefficient in SBM estimated for male and female broilers chickens was 0.419. Keywords: Digestibility. Phosphorus. Poultry. Soybean meal.